Stabilization of the Generalized Benders Decomposition applied to Short-Term Hydrothermal Coordination Problem - Rubiales, Aldo Jose (2013)
Solving the Short Term Hydrothermal Coordination (STHTC) Problem considers the resolution of both the Unit Commitment (UC) and the Economic Dispatch (ED) for thermal and hydraulic units. In order to avoid post-dispatch corrections, the transmission network is modeled with a high level of detail considering an AC power flow. These facts lead to a very complex optimization problem which is solved by using a novel decomposition approach which combines Generalized Benders Decomposition (GBD) with Bundle methods. This proposed method resembles a stabilized version of the cutting planes method, which drastically reduces the well-known tailing-off effect that Benders methods have. The approach presented in this work allows the decomposition of the whole problem in a quadratic mixed integer master problem, and in a non-linear subproblem which should be separable. The former defines the state and the active power dispatched by each unit whereas the latter determines the reactive power to meet the electrical constraints through a modified AC optimal power flow (OPF). These approaches were applied to a 9-bus test case, and to the IEEE 24-bus test case. The problem is solved for a time horizon of a day with a one-hour step.